Preparation via flocculation of reduced graphene oxide/cationic polyacrylamide composites and their electrochemical properties. Issue 106 (1st November 2016) - Wu, Li-Li; Deng, Fei-Rong; Zhang, Chao-Can
Abstract : We report a novel RGO/CPAM composite, fabricated on a gram scale, which has potential applications as an electrode material for use in supercapacitors. Abstract : Composites of reduced graphene oxide (RGO) and cationic polyacrylamide (CPAM) are prepared through a facile method. The effect of CPAM content on the specific capacitance of the composite is investigated. Compared with the pure RGO, the composite shows a relatively high capacitance, due to the fact that CPAM improves the wettability and surface area of RGO.